2009
DOI: 10.1039/b814407a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetism of decanuclear and octadecanuclear manganese(II/III) triethanolamine clusters

Abstract: Two new potential single molecule magnets [Mn(10)O(3)(O(2)CCH(3))(6)(tea)(teaH)(3)(teaH(2))(3)][NO(3)](2).3H(2)O (1) and [Mn(18)(N(3))(12)O(12)(tea)(2)(teaH)(4)(OMe)(MeOH)].2MeOH.H(2)O.Et(2)O (2) have been synthesised using manganese(II) nitrate, the tripodal ligand triethanolamine (teaH(3)) and co-ligands such as acetate for 1 and azide for 2. Both compounds are mixed-valent with 1 consisting of 4 Mn(II) and 6 Mn(III) ions and 2 consisting of 3 Mn(II) and 15 Mn(III) ions. Complex 1 has a near planar Mn(7)(II/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…The plots of M vs. H/T at different temperatures do not superpose on a single master curve, suggesting the presence of a significant anisotropy in 1 and/or the population of low‐lying excited states, which is expected to occur in Mn II /Mn III complexes . Indeed, the M–H isotherms at 1.8 and 2 K display an inflection point at about 20 kG and at a little above 10 Nµ B , indicating a spin change within the {Mn 6 } subunits.…”
Section: Resultsmentioning
confidence: 93%
“…The plots of M vs. H/T at different temperatures do not superpose on a single master curve, suggesting the presence of a significant anisotropy in 1 and/or the population of low‐lying excited states, which is expected to occur in Mn II /Mn III complexes . Indeed, the M–H isotherms at 1.8 and 2 K display an inflection point at about 20 kG and at a little above 10 Nµ B , indicating a spin change within the {Mn 6 } subunits.…”
Section: Resultsmentioning
confidence: 93%
“…For background to polynuclear chromium-containing complexes, see: McInnes et al (2005); Affronte et al (2005). For the use of amino alcohols with versatile bridging modes in generating such metal clusters, see: Langley et al (2009); Ferguson et al (2008); Saalfrank et al (2001). For background to direct synthesis, see: Kokozay & Shevchenko (2005).…”
Section: Related Literaturementioning
confidence: 99%
“…Winpenny and coworkers devoted to magnetic studies of high-nuclear cages and wheels (McInnes et al, 2005;Affronte et al, 2005). At the same time, the potential of alcohols and amino alcohols in generating such metal clusters was widely explored (Saalfrank et al, 2001;Langley et al, 2009;Ferguson et al, 2008).The polydentate alkoxo ligands possessing versatile bridging modes were recognized as promising reagents for synthesis of new heterometallic complexes. Previously we have demonstrated that amino alcohols represent a powerful tool for assembling polynuclear metal complexes in conditions of the synthetic approach named "direct synthesis of coordination compounds".…”
Section: S1 Commentmentioning
confidence: 99%
“…In the development of new synthesis routes, the selection of the organic ligands is extremely significant. Many ligands have been explored for the formation of 3d metal clusters with various topologies and magnetic properties, such as alcohol amines,17 pyridyl alcohols,18 pyridyl ketone oximes,19 salicylaldoximes,20 alkyl alcohols,21 aromatic alcohols,22 and so on 23,24…”
Section: Introductionmentioning
confidence: 99%